Responsibility Of Land Deed Officials In Preparing Sale Deeds Who Are Proven To Commit Crimes With Land Mafia - Tody Adi Pratama; Anriz Nazaruddin Halim; Khoirul Anwar (Journal of Innovative and Creativity, 2025)
The study purpose was to analyze the legal consequences arising from a deed of sale and purchase made by a Land Deed Making Officer (Pejabat Pembuat Akta Tanah/PPAT) who is proven to have committed a criminal act in collaboration with the land mafia, as well as to examine the scope of legal responsibility borne by the PPAT for such actions. This study highlights that errors committed by a PPAT, whether intentional or due to negligence, may contain criminal elements, particularly in cases involving falsified documents or the inclusion of false information in an authentic deed. The discussion is grounded in the theory of legal consequences proposed by Soeroso and the theory of legal responsibility developed by Hans Kelsen, which emphasize the linkage between unlawful acts and legal accountability. Materials and methods. This research employs a normative legal research method with a library research approach, relying on secondary data sources. The legal materials consist of primary legal materials in the form of legislation and court decisions, secondary legal materials including legal doctrines, books, and scholarly journals, as well as tertiary legal materials. The approaches used in this study include the statutory approach, the case approach, and the analytical approach. Data collection was conducted through identification and inventory of relevant legal norms and authoritative legal literature. Results. The findings indicate that a PPAT who is proven to have committed a criminal act in the performance of official duties may be subject to administrative sanctions imposed by the Minister, ranging from temporary suspension to honorable or dishonorable dismissal. In addition, the PPAT may incur criminal liability under Article 266 of the Indonesian Criminal Code due to the presence of malicious intent manifested in false statements within an authentic deed. Conclusions. The involvement of a PPAT in land mafia practices results in serious administrative and criminal consequences and undermines legal certainty in land administration, thereby necessitating strict professional integrity and compliance with applicable laws.